Inhibition of dimethyl sulfoxide-stimulated Friend cell erythrodifferentiation by hydrocortisone and other steroids. - Scher, W (1978)
Erythrodifferentiation and hemoglobin synthesis in dimethyl sulfoxide-stimulated Friend erythroleukemia cells were inhibited by hydrocortisone (HC) and four other steroids: dexamethasone, deoxycorticosterone, corticosterone, and aldosterone. The effect was specific, because no significant cytotoxicity occurred with any of these compounds at the concentrations that were inhibitory. The mechanism of action of HC was studied in detail. In the absence of dimethyl sulfoxide, it had no effect on hemoglobin levels; but, in the presence of this inducer, the synthesis of heme and globin were each inhibited by approximately 90%. There was no alteration in the synthesis of any major protein other than globin, as determined by gel electrophoresis of cell lysates. The activities of two enzymes in the heme biosynthetic pathway, delta-aminolevulinate dehydratase and uroporphyrinogen-I synthase, were inhibited by 80% and 70%, respectively. Globin mRNA induction was reduced by approximately 90%. This demonstrated that the HC inhibition of globin synthesis occurred at a pretranslational step. The dimethyl sulfoxide-induced single-stranded breaks in DNA, which have been suggested to play a role in Friend leukemia cell differentiation, were reduced in number but not eliminated. HC reduced the dimethyl sulfoxide-stimulation of virus release into the medium by approximately 50%. HC treatment in the absence of dimethyl sulfoxide doubled the production of virus.